Pengembangan Media Pembelajaran Berbasis Wordwall Terintegrasi Google Classroom Pada Mata Pelajaran Geografi Materi Dinamika Litosfer Kelas X Di SMA Negeri 5 Gorontalo Utara - Zulkriansyah, Zulkriansyah; Eraku, Sunarty Suly; Yusuf, Daud (Universitas Negeri Gorontalo, 2025)
The purpose of this research is to develop wordwall-based learning media integrated with google classroom on lithospheric dynamics material at SMA Negeri 5 North Gorontalo. The model used is the ADDIE development model, whose research includes 5 stages including analysis, design, development, implementation, and evaluation. The results of research on the development of learning media based on wordwall integrated google classroom on the material of lithospheric dynamics show the assessment of material experts which is 81% very feasible, the assessment of media experts 89% very feasible, the assessment of geography teachers 92% very feasible and the results of product trials on class X students of SMA Negeri 5 North Gorontalo. the results of student responses to learning media using Wordwall natural disaster mitigation material, namely by using a limited test of 78% and a general test getting 86%. So that learning media using Wordwall integrated Google Classroom can be used in the learning process in class related to natural disaster mitigation material. The conclusion of this research is that learning media is declared feasible to use in the learning process